PERANCANGAN SISTEM INFORMASI PELAPORAN MASYARAKAT UNTUK KERUSAKAN JALAN DI PONTIANAK MENGGUNAKAN GOOGLE MAPS API - Daniel Oktodeli Sihombing (Universitas Bina Sarana Informatika, 2016)
Web technologies have evolved very rapidly and have a positive impact on society. Information can be easily obtained by any society using mobile gadgets such as smartphones. Damage to roads is often a problem for people due to lack of valid information about it. Waterfall method used to develop application on this research. Google Maps allows users to access the world map with a smartphone via a web browser. Web browser will ask the user for permission to memproleh point locations that are stored on the smartphone's GPS display on the google map. Public reporting information system designed to combine Google Maps ability to translate latitude and longitude coordinates obtained from GPS smartphone to be displayed on the map. This system can display all the coordinate data from the database, where the data is obtained from the community and also report the coordinates of the road users who are accessing the system. Road conditions reporting feature has a simple interface to providing effective and efficient reporting. Upload photos done directly via the smartphone's camera that can reduce time to selecting photos to be uploaded. This information system can display data and image about roads damage in Pontianak and its coordinates on the map so users can be more vigilant in travel.